A Method For Detecting Duplicate And Near-Duplicate Images Penetration - Ramesh Shahabadkar, Dr.; S Sai Satyanarayana Reddy, Dr.; Devika, P. (International Journal of Engineering and Technology, 2018)
A method for detection of duplicate or near-duplicate image penetration from images in the similar group by distribution of color and other attributes of the image. Distinctive sceneries of the images penetration are identified. Each couple of images penetration with at least one distictive scenary is mutual; the distictive scenary of each image penetration is allied to normalize whether the couple is duplicates or near-duplicates.